Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe - Schmid-Egger, Christian; Straka, Jakub (Zootaxa, 2019)
Species of the genus Miscophus from Central, Northern, and Eastern Europe are reviewed and a new key to these species is presented. Miscophus cappadocicus de Beaumont, 1967 is given a new status of a valid species (described as a subspecies of Miscophus mavromoustakisi Andrade 1953). New synonyms for Miscophus albufeirae Andrade, 1952 are: Miscophus susterai Balthasar, 1953, M. unigena Balthasar, 1953 and M. albufeirae ssp. anatolicus de Beaumont, 1967. New synonyms for Miscophus insolitus Andrade, 1953 are: Miscophus insulicola Balthasar, 1953, Miscophus percitus Mokrousov, 2004. The following species are new in the fauna of Central Europe: Miscophus albufeirae Andrade, 1952 (Hungary), Miscophus cappadocicus de Beaumont, 1967 (Slovakia, Hungary), Miscophus johni Mokrousov, 2004 (Czech Republic), Miscophus minutus Andrade, 1953 (Hungary).